2022
DOI: 10.5194/bg-2021-336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable isotope profiles of soil organic carbon in forested and grassland landscapes in the Lake Alaotra basin (Madagascar): insights in past vegetation changes

Abstract: Abstract. The extent to which the central highlands of Madagascar were once covered by forests is still a matter of debate: while reconstructing past environments is inherently difficult, the debate is further hampered by the fact that the evidence documenting land cover changes and their effects on carbon and sediment dynamics in Madagascar has hitherto mainly been derived from lake coring studies. Such studies provide an integrated view over relatively large areas but do not provide information on how land u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Gillson, 2015; Mariotti & Peterschmitt, 1994). Razanamahandry et al (2022) have recently reported the first such study in Madagascar in the Lake Aloatra basin on the edge of the eastern forest belt. They found the grasslands in this study area had likely replaced forests.…”
Section: The Vegetation Of Pre‐contact Landscapesmentioning
confidence: 99%
“…Gillson, 2015; Mariotti & Peterschmitt, 1994). Razanamahandry et al (2022) have recently reported the first such study in Madagascar in the Lake Aloatra basin on the edge of the eastern forest belt. They found the grasslands in this study area had likely replaced forests.…”
Section: The Vegetation Of Pre‐contact Landscapesmentioning
confidence: 99%
“…With the exception of a few protected areas and high elevation sites, the majority of this ecoregion is currently covered by open grassland that is dominated by C 4 grasses and largely devoid of trees (reviewed in Lehmann et al, 2022). Yet numerous studies converge to suggest that forest cover was more widespread for much of the Holocene (Burney, 1987a(Burney, , 1987bCrowley, 2010;Crowley et al, 2021;Gasse & Van Campo, 1998;Gasse & Van Campo, 2001;Joseph & Seymour, 2020;Razanamahandry et al, 2022). These data include charcoal and pollen data from lake cores, as well as stable carbon isotope (δ 13 C) data from soils and animal remains.…”
Section: Introductionmentioning
confidence: 99%